2010
DOI: 10.1159/000319097
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a Parameter of Glomerular Filtration Rate in Patients with Ovarian Cancer

Abstract: Aims: To evaluate the potential role of serum cystatin C as a marker of renal function in patients with ovarian cancer. Methods: Treatment of consecutive ovarian cancer patients who were eligible for chemotherapy with paclitaxel (135 mg/m2/24 h) and cisplatin (75 mg/m2) every 3 weeks in 6 cycles. Glomerular filtration rate (GFR) markers, i.e. serum levels of creatinine and cystatin C, estimated by the Cockcroft-Gault and Modification of Diet in Renal Disease formulas, were recorded before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
0
18
0
2
Order By: Relevance
“…On the other hand, in a study regarding ovarian cancer patients who received paclitaxel-cisplatin combination, no correlation was noted between cystatin C and the other GFR markers (serum creatinine level, Cockcroft-Gault, and MDRD formulations). 24 In the same study, significant correlations were found between the cystatin C levels and pretreatment tumor dimension and also with CA 125 levels. As a cysteine protease inhibitor, cystatin C is elevated in the presence of this tumor, which might explain why the cystatin C level does not reflect GFR.…”
Section: Discussionmentioning
confidence: 78%
“…On the other hand, in a study regarding ovarian cancer patients who received paclitaxel-cisplatin combination, no correlation was noted between cystatin C and the other GFR markers (serum creatinine level, Cockcroft-Gault, and MDRD formulations). 24 In the same study, significant correlations were found between the cystatin C levels and pretreatment tumor dimension and also with CA 125 levels. As a cysteine protease inhibitor, cystatin C is elevated in the presence of this tumor, which might explain why the cystatin C level does not reflect GFR.…”
Section: Discussionmentioning
confidence: 78%
“…Kos et al reported that serum Cys-C levels were significantly higher in patients with advanced melanoma and colorectal cancer than in patients with primary melanoma and healthy controls (11,12). Other investigators, however, reported that Cys-C is not influenced by tumor extent (13). In malignancy, an imbalance between cysteine proteases and their inhibitors, associated with metastatic tumor cell phenotype, is thought to facilitate tumor cell invasion and metastasis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al reported that Cys-C concentrations have moderate associations with CRP and fibrinogen that are not dependent on CrCl (10). In addition, results of recent studies have shown a significant correlation between serum Cys-C levels and malignant progression in colorectal cancer, melanoma and ovarian cancer (11)(12)(13), although earlier studies reported that serum Cys-C levels were not affected by the presence of malignancies (14,15). With regard to serum Cys-C levels in patients with lung cancer, there is only one report by Naumnik et al (16).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , CysC secretion is not affected by cisplatin [18], but the effect of other anti-emetics on CysC production or release is unknown. In vitro , CysC transcription is increased in numerous cancer cell lines [38, 39], and in some patients with malignancy there is increased pCysC [40, 41], which has generally correlated with burden of disease [42, 43]. …”
Section: Discussionmentioning
confidence: 99%